2015
DOI: 10.1103/physrevlett.114.217001
|View full text |Cite
|
Sign up to set email alerts
|

Itinerant Ferromagnetism in the As4pConduction Band ofBa0.6K0.4Mn

Abstract: X-ray magnetic circular dichroism (XMCD) measurements on single-crystal and powder samples of Ba0.6K0.4Mn2As2 show that the ferromagnetism below TC ≈ 100 K arises in the As 4p conduction band. No XMCD signal is observed at the Mn x-ray absorption edges. Below TC, however, a clear XMCD signal is found at the As K edge which increases with decreasing temperature. The XMCD signal is absent in data taken with the beam directed parallel to the crystallographic c axis indicating that the orbital magnetic moment lies… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 35 publications
(74 reference statements)
4
28
0
Order By: Relevance
“…In particular, the As-4p electrons, with a small fraction near E F , could be spin-polarized. Such a nontrivial scenario was recently found and demonstrated in Ba 1−x K x Mn 2 As 2 which shows weak FM for x >0.19 [58][59][60] . Here the DOS of As-4p also shows a maximum at E F (the inset of Fig.…”
Section: E Density-functional Calculationsmentioning
confidence: 76%
“…In particular, the As-4p electrons, with a small fraction near E F , could be spin-polarized. Such a nontrivial scenario was recently found and demonstrated in Ba 1−x K x Mn 2 As 2 which shows weak FM for x >0.19 [58][59][60] . Here the DOS of As-4p also shows a maximum at E F (the inset of Fig.…”
Section: E Density-functional Calculationsmentioning
confidence: 76%
“…Although it cannot induce the band folding observed in BaMn 2 As 2 , a weak in-plane ferromagnetic component was reported in hole-doped Ba 1−x K x Mn 2 As 2 [22,23]. Although a theoretical study attributes the in-plane ferromagnetic component to a canting of the Mn moments [24], recent X-ray magnetic circular dichroism experiments rather suggest that the ferromagnetic component resides on the As 2p orbital [25]. In either cases, the magnetic structure in BaMn 2 As 2 is certainly prone to a distortion as compared to the simple G-type AFM of the Mn alone, which could possibly induce a band folding.…”
Section: Resultsmentioning
confidence: 99%
“…The X-ray magnetic circular dichroism experiment identified that the ferromagnetic moment arises from the As p orbitals and coexists with the AFM moment of Mn atoms [38]. Although the interplay of the magnetic hexadecapole order and the ferromagnetic order would be an interesting subject, it is left for a future study.…”
Section: B Hole-doped Bamn2as2mentioning
confidence: 97%